2021
DOI: 10.3390/jcm10215206
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sleep Disorders between HIV-Infected Persons and Matched Controls with Sleep Problems: A Matched-Cohort Study Based on Laboratory and Survey Data

Abstract: Objectives: Sleep disturbances are prevalent problems among human immunodeficiency virus (HIV)-infected persons. The recognition of comorbid sleep disorders in patients with HIV is currently hampered by limited knowledge of sleep-related symptoms, sleep architecture, and types of sleep disorders in this population. We aimed to compare the differences in sleep-related symptoms and polysomnography-based sleep disorders between HIV-infected persons and controls. Methods: The study evaluated 170 men with a Pittsbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“… Taibi et al (2013) suggested that “objective measures (polysomnography, actigraphy, sleep monitor) also show disruption of sleep onset and continuity as well as disruption of sleep stages.” Specifically, ( Faraut et al, 2021 ) defined sleep disturbance in HIV in terms of changes in sleep quality and sleep architecture observable using increases in the short-wave stage (SWS) of sleep, greater SWS during the latter half of the sleep period, and altered non-REM (NREM) and REM sleep cycles. These findings were echoed by Chen et al (2021) , who described similar objective characteristics of sleep disturbance in HIV based on polysomnography measurements, remarkably increased SWS during later sleep cycles, persistent alfa-intrusion into SWS, and suggestions of non-restorative sleep. Using actigraphy results, De Francesco et al (2021c) proposed that a sleep disturbance involved a longer sleep latency, shorter total sleep time, reduced sleep efficiency, and more time spent in stage 1 sleep.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“… Taibi et al (2013) suggested that “objective measures (polysomnography, actigraphy, sleep monitor) also show disruption of sleep onset and continuity as well as disruption of sleep stages.” Specifically, ( Faraut et al, 2021 ) defined sleep disturbance in HIV in terms of changes in sleep quality and sleep architecture observable using increases in the short-wave stage (SWS) of sleep, greater SWS during the latter half of the sleep period, and altered non-REM (NREM) and REM sleep cycles. These findings were echoed by Chen et al (2021) , who described similar objective characteristics of sleep disturbance in HIV based on polysomnography measurements, remarkably increased SWS during later sleep cycles, persistent alfa-intrusion into SWS, and suggestions of non-restorative sleep. Using actigraphy results, De Francesco et al (2021c) proposed that a sleep disturbance involved a longer sleep latency, shorter total sleep time, reduced sleep efficiency, and more time spent in stage 1 sleep.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, the authors disagreed on how sleep disturbances among the PLWH population were identified. Chen et al (2021) concluded that limited data characterizes the type of sleep disturbance in these patients. Previous studies have not yielded consistent results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations